Utilization of unmanned aerial vehicles in geothermal exploration: A review. Issue 1 (February 2021) - Marwan; Noviandy, T R; Maulana, A; Suhendra, R; Yusuf, M; Lala, A; Idroes, G M; Muslem; Mahmudi; Idroes, R
Abstract: Geothermal is a source of heat energy from the earth and is a renewable energy source. Geothermal exploitation as an energy source is still ongoing. Recently there has been an increase in the use of an unmanned aerial vehicle (UAV) technology as an alternative option in aerial surveys and observations in geothermal areas. The use of UAVs in geothermal exploration is an alternative option. This is because the unmanned aerial vehicle has many advantages and features that can be utilized. Various studies that have been conducted have shown that the use of UAVs has become a method that brings changes in the exploration process of geothermal areas. UAVs are proven to assist in the geothermal exploration process and produce fast, reliable, and cost-effective solutions. UAVs also help explore geothermal areas that were previously difficult to study, namely areas with extreme environmental conditions and rugged access terrain. UAVs can also be used to search for potential sources as new manifestations in geothermal areas so that the points of manifestation in geothermal areas can be identified. This is very helpful in increasing the efficiency and less risk for the researcher.